Proceedings of the third International Workshop of the IFIP WG5.7 Special interest group on Advanced techniques in production planning & control. 24-25 February 2000, Florence, Italy - Tucci, Mario; Garetti, Marco (Proceedings e report, 2002)
Contents of the papers presented at the international workshop deal with the wide variety of new and computer-based techniques for production planning and control that has become available to the scientific and industrial world in the past few years: formal modeling techniques, artificial neural networks, autonomous agent theory, genetic algorithms, chaos theory, fuzzy logic, simulated annealing, tabu search, simulation and so on. The approach, while being scientifically rigorous, is focused on the applicability to industrial environment.